Determinants of poverty in Egypt, 1997 - Datt, Gaurav; Jolliffe, Dean (International Food Policy Research Institute, 1999)
Poverty profiles are a useful way of summarizing information on the levels of poverty and the characteristics of the poor in a society. For Egypt, while there has been some work on a descriptive analysis of the characteristics of the poor, to our knowledge, there is no precursor to an empirical modeling of the determinants of poverty using nationally representative data. In this paper, we have sought to extend the descriptive analysis of the Egypt poverty profile presented in Datt, Jolliffe, and Sharma (1998) by modeling the determinants of poverty, using data from the 1997 Egypt Integrated Household Survey. A key conclusion of our study has to do with the important instrumental role of education in alleviating poverty in Egypt. Increasing average years of schooling, as well as improving the level of parents education, is indicated to have large impacts on average living standards and poverty levels.